Assessment of 1 mg Dexamethasone Suppression Test in Patients with Obesity Before Bariatric Surgery - YAVUZ, DİLEK (SPRINGER, 2020)
Purpose This study aims to examine the prevalence of Cushing's syndrome (CS) in class 3 obese patients before bariatric surgery. Materials and Methods The data of 1037 class 3 obese patients admitted to the endocrinology outpatient clinic for endocrinological evaluation before bariatric surgery between 2012 and 2019were reviewed retrospectively. One milligram dexamethasone suppression test (DST) was used for the evaluation of hypercortisolism in all cases and cutoff accepted as 1.8 mu g/dL. Results The mean body mass index (BMI) was 48 +/- 8.9 kg/m(2)and age was 42 +/- 10 years with female preponderance (F/M: 799/238] being observed in this cohort. Insufficient cortisol suppression was found in 40 patients; confirmed hypercortisolemia was detected in 8 patients. The prevalence of pathologic DST was 3.85% and 0.77% in confirmed hypercortisolism. The specificity for 1-mg DST with the cutoff 1.8 mu g/dL was calculated as 96.8%. Conclusion Hypercortisolism prevalence was found to be low, and 1 mg DST is a sufficient test for the screening of CS in class 3 obese patients evaluated before bariatric surgery.
Keywords: Morbid obesity; Cushing's syndrome; Hypercortisolism; CLINICAL-PRACTICE GUIDELINE; TYPE-2 DIABETES PATIENTS; CUSHINGS-SYNDROME; EUROPEAN-SOCIETY; DIAGNOSIS; HYPERCORTISOLISM; PREVALENCE; MANAGEMENT; AXIS